2021
DOI: 10.1097/md.0000000000025623
|View full text |Cite
|
Sign up to set email alerts
|

Differences in microbiota between acute and chronic perianal eczema

Abstract: Microbiota has been suggested to play a role in patients with intestinal and cutaneous diseases. However, the profiling of perianal eczema microbiota has not been described. We have explored the general profile and possible differences between acute and chronic perianal eczema. A total of 101 acute perianal eczema (APE) and 156 chronic perianal eczema (CPE) patients were enrolled in this study and the perianal microbiota was profiled via Illumina sequencing of the 16S rRNA V4 region. The microbial α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…In this study, the authors concluded that, in acute lesions of AD patients, there is a more direct damage to the epidermal skin barrier, mainly through scratching, and S. aureus can more easily penetrate or colonise the skin than in chronic lesions, which can also explain this association in HE patients. Another study showed a similar finding in patients with acute and chronic perianal eczema 23 . This finding may enable a personalised treatment of the patients depending on the clinical symptoms of the disease.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…In this study, the authors concluded that, in acute lesions of AD patients, there is a more direct damage to the epidermal skin barrier, mainly through scratching, and S. aureus can more easily penetrate or colonise the skin than in chronic lesions, which can also explain this association in HE patients. Another study showed a similar finding in patients with acute and chronic perianal eczema 23 . This finding may enable a personalised treatment of the patients depending on the clinical symptoms of the disease.…”
Section: Discussionsupporting
confidence: 60%
“…Another study showed a similar finding in patients with acute and chronic perianal eczema. 23 This finding may enable a personalised treatment of the patients depending on the clinical symptoms of the disease.…”
Section: S Aureus Colonisation and Acute Versus Chronic He Symptomsmentioning
confidence: 95%
“… 9 , 14 Posterior to the vulva, the perineal skin and microbiota are underappreciated modulators of genital health. 15 23 …”
Section: The Persisting Language Biasmentioning
confidence: 99%
“…The imbalance of gut microbiota can cause a series of diseases, including digestive system diseases, metabolic diseases, inflammatory bowel disease, irritable bowel syndrome, and autoimmune diseases [16][17][18]. Anus is the gateway of digestive tract to the outer body and the perianal diseases are closely related to the microorganisms [19]. At present, the correlations between the perianal abscesses and gut microbiota are not fully understood.…”
Section: Introductionmentioning
confidence: 99%